FRI0196 Real-World Impact of Taiwan Health Policy on Dose Tapering and Withdrawing Biologics in Rheumatoid Arthritis Patients: A Retrospective Chart Review Study. (15th July 2016) - Chang, C.; Chen, K.; Chen, Y.; Cheng, T.; Hsu, P.; Lai, N.; Lan, J.; Lee, C.; Lee, S.; Lin, H.; Tsay, G.; Yen, J.; et al.
Abstract : Background: The OuT comes A ssociated with taP ering biologics among patiE nts with R heumatoid arthritis (TAPER) study is a multicenter retrospective chart review to assess real-world implication of the Taiwan National Health Insurance Administration policy on tapering and withdrawing biologics in stable rheumatoid arthritis (RA) patients. Objectives: To assess the clinical and health resource utilization (HRU) outcomes associated with dose tapering and withdrawing of biologics among stable RA patients. Methods: Medical chart data were collected from RA patients tapering adalimumab (ADA) or etanercept (ETN) who had been on the treatment for ≥2 years prior to tapering. RA disease flares and HRU were assessed for the 6-month pre-tapering period, and for the 6-month short-term and up to 18-month longer-term post-tapering periods. A flare was defined a priori as any of the following: 1) an increase in DAS28 ≥1.2; 2) an increase in the number of swollen/tender joints; or 3) use of injectable steroids during outpatient or emergency room (ER) visits. Results: Data were collected from medical charts of 261 patients (ADA=106, 40.6%; ETN=155, 59.4%). The majority were female (76.2%), with a mean age of 57.2±13.0 years, and an average RA duration of 10.1±5.6 years. Hypertension (31.4%), osteoporosis (19.2%), other autoimmune diseases (16.9%), and dyslipidemia (14.2%) were the most common comorbidities. More than half of the patients had a longer-term follow-up between one year and18 months (58.6%: ADA=62, 40.5%; ETN=91, 59.5%). The majority of ADA patients were tapered to 40mg every three weeks (63.6%) or 40mg every four weeks (30.8%); most ETN patients were tapered to 25mg every 5 days (49.4%) or once a week (30.5%). Greater proportions of patients had an RA flare post-tapering (pre-tapering: 20.7%; post-tapering short-term: 44.1%; post-tapering longer-term: 73.9%). When compared to the pre-tapering period, the mean RA flare events per patient per year increased substantially post-tapering (pre-tapering: 0.5; post-tapering short-term: 1.2; post-tapering longer-term: 1.6, all p<0.001). Patients had increased office visits during the short-term (pre: 1.2 vs. post: 1.4 per patient per month, p<0.001). Conclusions: Tapering biologic agents among stable RA patients may lead to an increase in RA flare and an increase in outpatient visits. Disclosure of Interest: C. Chang: None declared, K. Chen: None declared, Y. Chen: None declared, T. Cheng: None declared, P. Hsu: None declared, N. Lai: None declared, J. Lan: None declared, C. Lee: None declared, S. Lee: None declared, H. Lin: None declared, G. Tsay: None declared, J. Yen: None declared, C. Tsai Shareholder of: AbbVie, Employee of: AbbVie, Y. Bao Shareholder of: AbbVie, Employee of: AbbVie, M. Skup Shareholder of: AbbVie, Employee of: AbbVie, M. Yang Employee of: Analysis Group, E. Wu Employee of: Analysis Group, V. Garg Shareholder of: AbbVie, Employee of: AbbVie